2006
DOI: 10.1177/0021998305057434
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of an Artificially Aged (T6) Al–Si–Mg-based Metal Matrix Composite

Abstract: The influence of age hardening on the corrosion behavior of Al-Si-Mg-based metal matrix composites (MMCs) has been investigated in aerated and deaerated 3.5 wt% aqueous NaCl solutions. Silicon carbide particle (SiC p ) reinforced composites consisting of 10 and 20 vol% SiC p s are produced by the compocasting technique. After the extrusion process, the composites are artificially aged (T6). The corrosion resistances of the aged composites are analyzed by measuring the cyclic potentiodynamic polarization. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The details of the production and experimental methods are given in the previous study. 15 The proposed ANN model for the prediction of corrosion susceptibilities of the composites is formed by using the software MATLAB program (version 7.9.0.529, R2009b). The number of hidden layers and the number of neurons within these layers are optimized through the training process.…”
Section: Modeling With Annmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the production and experimental methods are given in the previous study. 15 The proposed ANN model for the prediction of corrosion susceptibilities of the composites is formed by using the software MATLAB program (version 7.9.0.529, R2009b). The number of hidden layers and the number of neurons within these layers are optimized through the training process.…”
Section: Modeling With Annmentioning
confidence: 99%
“…15,16 An ANN was used in order to predict the occurrence of general or localized corrosion, using potentiodynamic polarization scans. The initial data inputs such as E corr , E pit , and I corr were calculated from polarization scans for a number of different compositions, and these were used for the predictions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exhibit high strength, stiffness and superior wear resistance, therefore these composites have received considerable interest and wide range of applications in automotive, aerospace and transport industries [1][2][3][4]. Among these reinforcements titanium diboride (TiB 2 ) is an advanced ceramic material with relatively high strength and durability as characterized by high melting point, hardness, strength to density ratio, and wear resistance [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The higher nucleation vacancy promotes the creation of Guinier-Preston (GP) zone such as Al-Mg-Si and Mg-Al alloy. [6] Transmission electron microscopy (TEM) studies have proved the existence of dislocation due to heterogeneous nucleation which leads to increase the strength of the Al MMCs [7]. Many research work showed that precipitation reaction in some Al MMCs in both theoretical and experimentally and they suggested that only matrix dislocation enhances the precipitation growth [8].…”
Section: Introductionmentioning
confidence: 99%